Teacher agency within the Finnish CLIL context: tensions and resources. Issue 5 (4th July 2019) - Pappa, Sotiria; Moate, Josephine; Ruohotie-Lyhty, Maria; Eteläpelto, Anneli
ABSTRACT: Recent discussion indicates that the initial enthusiasm of Content and Language Integrated Learning (CLIL) teachers can be undermined by the demands of foreign-language mediated education. However, there is a lack of research on the resources and tensions that respectively support or limit the professional agency of CLIL teachers. By means of semi-structured interviews with fourteen participants, this study seeks to better understand how teacher agency is experienced by CLIL teachers working in Finnish primary schools. To examine tensions and resources in CLIL teachers' work lives, a holistic and dynamic theoretical conceptualization of teacher agency is suggested, paying particular attention to the classroom, professional relationships and the wider sociocultural environment. Findings showed that language, classroom-related tensions and temporal, material and developmental resources were perceived as tensions limiting teacher agency. In contrast, autonomy, openness to change, teacher versatility, and collegial community were found to support teacher agency. The study concludes with practical implications for teacher education, practicing teachers and future research.